Listrik Tenaga Surya untuk Pompa Submersible pada Greenhouse Hidroganik di Kabupaten Malang - Hery Budiyanto; Pindo Tutuko; Aries Boedi Setiawan; Razqyan Mas Bimatyugra Jati; Muhammad Iqbal (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
This service activity is the application of an innovative submersible solar pump in a hydro-organic greenhouse environment in Grangsil Jambangan, Malang Regency. This is motivated by the need for water that can only be obtained through deep wells with submersible pumps in hydro-organic greenhouses that already use solar power plants but have insufficient power. The purpose of this service is to provide theoretical and practical understanding for Tour conscious group (POKDARWIS) Jambangan members as managers of the hydro-organic greenhouse. The methods used include focus group discussions (FGD) and joint practice in developing solar power plants for submersible pumps. After the implementation of this program, there was an increase in the capacity of the solar power plants, which has been able to turn on submersible pumps, hydroganic circulation pumps, and other needs. In one day, the submersible pump only needs to be turned on for 2 hours and produces 4,572 liters of water, sufficient for greenhouse hydroganic needs and other needs. Another positive impact is that POKDARWIS Jambangan members have been able to manage and maintain PLTS for a hydro-organic greenhouse. The submersible water pump prototype for hydroganic agriculture at the greenhouse using independent energy is very practical and efficient so it is expected to become a prototype for modern agricultural facilities in the context of a national-scale food security improvement program.